Análise da relação entre variação dos gastos com remuneração e desempenho organizacional financeiro - Loli, Dayane Andressa (2016)
It´s a recurrent concerning in Business Administration, and many studies and discussions have been carried out, in order to develop tools and practices to improve organizational performance. This dissertation had as main goal to investigate one of the factors that, probably, may contribute to increase de organizational performance and are frequently not taken as important by managers: the remuneration. It was attempted to identify a possible correlation between spends with remuneration and indexes of profitability of the companies. In methodology, it was used exploratory research with a quantitative approach. The data were taken from BM&F Bovespa, among 38 companies classified as belonging to a non-cyclical consumer subsector. The data gathering was made using documental analysis, only secondary ones. To provide higher consistency to conclusions, data were subjected to a statistical treatment using multivariate analysis. It was applied techniques like Pearson´s Correlation and Linear Regression to identify a relation between the values of spending with remunerations and organizational performance. The statistical analysis was generated with aid of SPSS 20.0 software. It was researched the following hypothesis: there are evidences pointing to conclusion that remuneration spending contribute to improve the corporative profitability. The hypothesis was confirmed. Therefore, it was possible to conclude that remuneration spending has correlation with the performance of the profitability of the companies.